A LEGAL STUDY ON JUVENILE RIGHTS WITH REF TO POCSO - Yadav, Rinki (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Protection of Children from Sexual Offences Act (POCSO), enacted in 2012 in India, marks a significant step in safeguarding juvenile rights and ensuring justice for victims of sexual offenses. This study critically examines the provisions, implementation, and implications of POCSO with a focus on juvenile rights. It explores the legal framework, judicial responses, and societal impact, while addressing challenges such as delayed justice, lack of awareness, and the need for systemic reforms. Through an analysis of case laws, data, and interviews, this research underscores the role of POCSO in protecting minors while suggesting avenues for its effective implementation.